Liberation from Dialysis Dependence in a Patient with HIV-Associated Nephropathy (HIVAN) after Combined Antiretroviral Therapy (cART). (16th March 2020) - Ramoutar, Virin; Makary, Raafat; Ravi, Malleswari; James, Leighton; Heilig, Charles
Abstract : Prior to the advent of combined antiretroviral therapy (cART), human immunodeficiency virus-associated nephropathy (HIVAN) was inevitably associated with rapidly progressive renal failure and dialysis dependence. HIV-1 seropositive patients often met with untimely deaths due to complications of end-stage renal disease (ESRD), opportunistic infections, or other HIV-related end-organ failure. Although the association between cART and improved outcomes in HIVAN has been recognized for over 20 years, no randomized trials have specifically examined this effect to date. In terms of reversal of dialysis-dependent renal failure after cART initiation, only a handful of case reports exist. The authors report a case of a 44-year-old Latino male requiring thrice-weekly haemodialysis in the setting of biopsy-proven HIVAN who was able to stop dialysis in 7 months after being initiated on cART.